A rede de atenção psicossocial e o cuidado ao paciente em sofrimento psíquico do município de Araraquara - Lughi, Aliceia Celene (2018)
Considering the preoccupations with the advances and limits of the RAPS, which subsidizes strategies for a territorialized intervention and based on the offer of a continuous care to the subject in psychological distress, the present research proposes to map and describe the operation of the equipment that compose the RAPS in the municipality of Araraquara-SP. It aims to describe and understand the care of people in psychiatric crisis in the RAPS, in order to investigate the different strategies of care of the services that comprise it, considering the conceptions and experiences of coordinators, managers and health professionals. It is an empirical research, with a qualitative-interpretative approach, having as field the RAPS of Araraquara -SP and as corpus of analysis the experiences of managers and health professionals. It was carried out a survey and characterization of the health equipment regarding the structure, work model and clinic offered, besides the different care strategies in crisis situation. The instruments constructed and used by the research were a semi-structured interview script, applied to 19 professionals / managers of RAPS services, and another script with RAPS user. The data were recorded and transcribed literally, and the analysis was based on the Thematic Content Analysis technique (MINAYO, 2014; BARDIN, 1979). The results were systematized in two large groups: I) described: characterization of the participants, description of the participating teams, performance of the participating teams, and training strategy; II) analytic: cores of sense distributed in thematic categories. The descriptive data indicate that the great majority of the participants are women, between 31 and 37 years old, are of the following careers, in descending order: nursing, psychology, occupational therapy, physical education and pharmacy. Many professionals (11) accumulate management function with care work. The equipment represented by the interviews was distributed as follows: Basic Care (9), CAPS (4), Urgency and Emergency (2), hospital care (2). The analytical data resulted in the following thematic categories: I dilemmas and barriers in relation to mental health care, II articulation between the health services that make up the RAPS, IIIexperience with RAPS users.The health equipment faces several dilemmas and obstacles that hamper the actions of care prevented the strengthening and the networking, being the lack of communication one of the most compromising factors. The articulation between health equipment and management is fragile and it is necessary that there be public investments in management strategies such as integrated planning, institution of flows, protocols and service agreement. The experience with a user of the RAPS equipment reveals that the subject is waiting for a long period of consultation with psychiatrists that results in hospitalization, demonstrating the fragmentation of care.